Anomalous Resistance Hysteresis in Oxide ReRAM: Oxygen Evolution and Reincorporation Revealed by In Situ TEM. Issue 23 (18th April 2017) - Cooper, David; Baeumer, Christoph; Bernier, Nicolas; Marchewka, Astrid; La Torre, Camilla; Dunin‐Borkowski, Rafal E.; Menzel, Stephan; Waser, Rainer; Dittmann, Regina
Abstract : The control and rational design of redox‐based memristive devices, which are highly attractive candidates for next‐generation nonvolatile memory and logic applications, is complicated by competing and poorly understood switching mechanisms, which can result in two coexisting resistance hystereses that have opposite voltage polarity. These competing processes can be defined as regular and anomalous resistive switching. Despite significant characterization efforts, the complex nanoscale redox processes that drive anomalous resistive switching and their implications for current transport remain poorly understood. Here, lateral and vertical mapping of O vacancy concentrations is used during the operation of such devices in situ in an aberration corrected transmission electron microscope to explain the anomalous switching mechanism. It is found that an increase (decrease) in the overall O vacancy concentration within the device after positive (negative) biasing of the Schottky‐type electrode is associated with the electrocatalytic release and reincorporation of oxygen at the electrode/oxide interface and is responsible for the resistance change. This fundamental insight presents a novel perspective on resistive switching processes and opens up new technological opportunities for the implementation of memristive devices, as anomalous switching can now be suppressed selectively or used deliberately to achieve the desirable so‐called deep Reset. Abstract : In situ transmission electron microscopy of memristive devices —a highly attractive candidate for next‐generation nonvolatile memory—reveals a previously unknown anomalous resistive switching mechanism. The resistance change is caused by an increase (decrease) in the overall concentration of oxygen vacancies within the device after positive (negative) biasing due to electrocatalytic release and reincorporation of oxygen at the electrode/oxide interface.